THE INFLUENCE OF CAREER DEVELOPMENT ON TEACHER PERFORMANCE AT BINONG PERMAI SMP - Nurhidayah, Arvin Septian; Liastuti, Erlina; Muljadi, Muljadi (Univesitas Muhammadiyah Tangerang, 2023)
Education is one of the studies that has received much attention from scientists. This is because of its very strategic role in improving human resources, Islamic education also gets various kinds of attention, especially in various complex problems that require immediate handling. Teacher problems are in the spotlight, because teachers are the spearhead of any policy or related to education. It is the teacher who will carry out operationally all forms of pattern, movement and movement of change in the world of education. Given the great role of the teacher, teachers are required to pay maximum attention to the development and quality of education. But the problem is, the teacher's own condition has not supported much in that direction, both in terms of quality, professionalism, quantity, and welfare. This research is a qualitative research that aims to determine the effect of career development on teacher performance at SMP BINONG PERMAI. The results of this research indicate that career development is carried out based on qualifications, competence, performance appraisal and the needs of government agencies through mutation mechanisms, promotions in accordance with applicable regulations.Keywords: Career Development and Teacher Performance